Synthesis of 1,2,3-triazole derivatives based on propargyl ester of a saturated single-basic carbonic acid and para-azidobenzoic acid - Azizovich Ibragimdjan Аbdugafurov; Bakhtiyarovich, Fazliddin Qirgizov; Sobirovich Ilhom Оrtikov (European Journal of Chemistry, 2021)
The development of highly effective and low-toxicity nonsteroidal anti-inflammatory drugs (NSAIDs) is one of the important challenges facing modern pharmacology. To overcome this problem, many studies have been conducted on compounds containing a five-membered heterocycle containing three nitrogen atoms. The pharmacodynamics of these compounds are mainly due to their anti-inflammatory effect. Therefore, it is important to synthesize new derivatives of 1,2,3-triazoles, to determine their structure and to look for substances with anti-inflammatory activity on their basis. For the first time, the corresponding derivatives of 4-(4-(exchangeable)-1H-1,2,3-triazole-1-yl)-benzoic acid were synthesized by cycloaddition of propargyl esters of saturated carboxylic acids and para-azidobenzoic acid in the presence of copper (I) iodide. The structure of the obtained substances was analyzed by IR, 1H NMR, and MS techniques. It is proved that under the action of the catalyst in the reaction, only 1,4-isomers are formed. Factors affecting the course of the reaction were identified. Only one isomer is formed in the reaction of cyclic addition under the action of a catalyst and the effect of temperature, duration of time, and nature of the solvent on the reaction yield was studied.